Inhalation of Ultrafine Zinc Particles Impaired Cardiovascular Functions in Hypertension-Induced Heart Failure Rats With Preserved Ejection Fraction - Bing, Fangbo; Wang, Xuan; Shen, Wenzeng; Li, Li; Niu, Pei; Chen, Ying; Zhang, Wenxi; Tan, Wenchang; Huo, Yunlong (Frontiers in Bioengineering and Biotechnology, 2020)
Although it is possible for inhalation of ultrafine particles to impair human health, its effect is not clear in patients with HFpEF. This study investigated cardiac and hemodynamic changes in hypertension-induced rats of HFpEF after inhaling ultrafine zinc particles for a while. Multiple experimental measurements were carried out in DSS rats fed with high salt (HS) and low salt (LS) diets as well as HS diet with the inhalation of ultrafine zinc particles (defined as HP). Cardiac strain and strain rate were quantified by the speckle tracking echocardiography. The pressure and flow waves were recorded in the carotid artery and abdominal aorta and analyzed by the models of Windkessel and Womersley types. HS and HP rats were found to show lower strains on endocardium and epicardium than LS rats. The inhalation of ultrafine zinc particles further reduced the strain in the longitudinal direction on the endocardium of rats with HFpEF, but had relatively small effects on the epicardium. The inhalation of ultrafine zinc particles resulted in the increase of systemic resistance and the decrease of total vascular compliance as well as the increased PWV and induced more severe vascular stiffening in rats with HFpEF. In summary, the inhalation of ultrafine zinc particles deteriorated local myocardial dysfunctions in the LV and the hemodynamic environment in peripheral arteries in rats of HFpEF. This study is of importance to understand the mechanisms of cardiovascular impairments owing to air pollution.